Gas-fueled steam generating units mathematical simulation for trainers of boiler room operators - Holovchenko, O. M.; Studynskyi, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Operations associated with run-up of industrial heating boiler room are considered. Method of logic-numeral simulation of power generation for staff training is described. Mathematical model of flow diagram of boiler room and its equipment is developed and analyzed.